EP 48. Local field potential oscillations of the globus pallidus in cervical and tardive dystonia. Issue 9 (September 2016) - Trenado, C.; Hartmann, C.; Elben, S.; Pauls, K.A.M.; Friggemann, L.; Groiss, S.J.; Timmermann, L.; Vesper, J.; Schnitzler, A.; Wojtecki, L.
Abstract : Reports about neural oscillatory activity in the globus pallidus internus (GPi) have targeted general (GD) and cervical (CD) dystonia, however they are nonexistent for tardive dystonia (TD). Sensory tricks (geste antagoniste) emphasize a role of sensory processing in CD rather than TD, however neural oscillatory correlates of that phenomenon have not been investigated. Here, we recorded local field potentials (LFPs) from seven CD and five TD patients intraoperatively. We compared LFP power in thetadelta, alpha and beta band during rest and sensory palmar stimulation (SPS) in patients with general anesthesia and local/analgo sedation. We found prominent thetadelta power activity in both CD and TD. Unlike TD, a significant difference between rest and SPS was revealed for CD. Our data support the presence of LFP oscillatory activity in CD and TD, while emphasizing thetadelta modulation of LFP power in CD as a putative signature of sensory tricks.